2
$\begingroup$

I think my homework about entropy is formulated incorrectly.

The question is the following:

let $X$ be a discrete random variable. Show that the entropy of a function $g$ of $X$ is less than or equal to the entropy of $X$ by justifying the following steps:

\begin{align} H(X) & = H(X)+H(g(X)\mid X)\\[8pt] & = H(X,g(X))\\[8pt] & = H(g(X)) + H(X\mid g(X))\\[8pt] & \geq H(g(X)) \end{align}

All the passages seem obvious except the first one. Isn't this entailing that $H(g(X)\mid X) = 0$, since entropy is always non-negative? How can this be a generally valid statement?

All I can think is the following:

$$ H(g(X)\mid X) = \sum_x P(X=x)H(g(X)\mid X=x)\\ = - \sum_{x_1} p(x_1) \sum_{g(x_2)} p(g(x_2)\mid x_1)\log p(g(x_2)\mid x_1) $$

How is this quantity $0$?

$\endgroup$
1
  • $\begingroup$ I expect that somewhere before that it was proved as a lemma that $H(Y|X)=0$ when $Y$ is a function of $X$. $\endgroup$ Nov 12 '14 at 0:38
5
$\begingroup$

It is because $\mathsf P(g(X)=g(x_2) \mid X=x_1)$ will equal either $1$ or $0$, and since we use the convention that $0 \log 0 = 0$, then it follows that $H(g(X) \mid X) = 0$.

$$\begin{align} \because p(g(x_2)\mid x_1) & = \begin{cases} 1 & : g(x_2)=g(x_1) \\ 0 & : g(x_2)\neq g(x_1) \end{cases} \\[2ex] p(g(x_2)\mid x_1) \log p(g(x_2)\mid x_1) & = 0 \\[4ex] \therefore H(g(X)\mid X) & = \sum_{x_1} p(x_1) H(g(X)\mid X=x_1) \\[1ex] & = - \sum_{x_1} p(x_1)\sum_{x_2}p(g(x_2)\mid x_1)\log p(g(x_2)\mid x_1) \\[1ex] & = 0 \end{align}$$


Remark As MHS points out, this result should match our intuition. If entropy measures disorder, then the entropy of $g(X)$ when conditioned on $X$ should have none such; as $g(X)$ has exactly one value for any given value of $X$.

Knowledge of a random variable entirely determines knowledge of the function of the random variable.

$\endgroup$
3
$\begingroup$

Think of entropy as randomness or disorder. Now if $X$ is known, then $g(X)$ can be evaluated and thus is also known. Hence the conditional entropy of $g(X)$ given $X$ is zero, as $g(X)$ can be deduced from the already given knowledge of $X$.

Of course if you want the technical proof, the answer below gives the corresponding formulas. However, often it is useful to first get a "feeling" about what entropy means in order to deduce what statements could be true whereas the proofs sometimes do not show this intuition behind the concept of entropy.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.